Therapie der systemischen Sklerose-assoziierten interstitiellen Lungenerkrankung - Prasse, A.; Bonella, F.; Müller-Ladner, U.; Witte, T.; Hunzelmann, N.; Distler, Jörg (Zeitschrift für Rheumatologie, 2019)
Background: Systemic sclerosis (SSc) is a fibrosing autoimmune disease of the connective tissue. In addition to skin fibrosis, pulmonary involvement and interstitial lung disease (ILD) in particular are the most common and severe manifestations of SSc. The disease is associated with a substantial risk of morbidity and mortality, especially in progressive ILD. In the last 5 years new treatment concepts for SSc-ILD have been investigated in numerous clinical studies. Material and methods: This review is based on a literature search in PubMed, focusing on the most relevant papers published up to the end of 2018 with the keywords “SSc” and “treatment”. Results: The treatment of SSc-ILD has changed over the last few years due to the results of many clinical studies. The updated guidelines of the European League Against Rheumatism (EULAR) recommend the use of cyclophosphamide or hematopoietic stem cell transplantation. Data for a positive influence on SSc-ILD are also available for mycophenolate, tocilizumab and anabasum. Because of the pathophysiological similarities to idiopathic pulmonary fibrosis, the use of the antifibrotic agents nintedanib and pirfenidone is currently being investigated in randomized, multicenter clinical trials and could be a novel and promising therapeutic strategy. Conclusion: Current drug studies may provide innovative therapeutic perspectives for SSc-ILD and could significantly improve the prognosis of affected patients in the future.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Connective tissue disease; Interstitial lung disease; Organ involvement; Systemic sclerosis; Therapy